Evaluation of the Effects of Varicoceles and Fertility Status on Volumetry and Shear-wave Elastography - Mustafa Özdemir; Ali Koç; Mustafa Bilgili; Gamze Türk (Genel Tıp Dergisi, 2022)
Aim: This study aims to compare the volumetry and shear-wave elastography findings in infertile and fertile patients and evaluate the effect of presence of varicoceles on the parameters. Materials-Methods: 40 infertile and 20 fertile patients (120 testes) (mean age 29,3±6,7) between January 2018-November 2018 were included in this prospective study. All patients underwent testicular B-mode and doppler ultrasonography (US) and shear-wave elastography (SWE). Patients were sub-grouped according to fertility status and presence or absence of varicoceles. Results: Testis stiffness was significantly higher in testes without varicoceles than those with varicoceles (p=0.021). It was also higher in fertile patients than infertile patients (p=0.015). Testes volumes were higher in fertile patients and patients with varicoceles (p=0.011 and p=0.028, respectively). Conclusion: SWE is a non-invasive, cheap and reproducible technique with promising results for diagnosis and follow-up in the evaluation of infertility.